Devising a methodology for estimating the information potential of energy enterprises under the conditions of digital coherency - Prokhorova, Viktoriia; Budanov, Oleksandr; Budanov, Pavlo; Slastianykova, Krystyna (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of assessing the level of information potential of energy enterprises under the conditions of digital coherence. The problem of effective management of the information potential of energy enterprises is solved on the basis of devising a methodology for assessing the level of information potential of energy enterprises under the conditions of digital coherence, taking into account modern challenges associated with the integration of digital systems. The methodology makes it possible to ensure the accuracy of analysis, prompt decision-making, and adaptation to the dynamic conditions of digital transformation. The devised methodology is based on interrelated stages, including the integration of indicators, assessment of the interaction of system components, and monitoring changes in indicators of the information potential of energy enterprises. The main stages of the methodology are selection of components of the information potential, such as the level of automation, IT infrastructure, staffing, information security, and digital systems; analysis of their interaction; monitoring and management of risks in real time. It was determined that the application of the methodology makes it possible to identify the weaknesses of the enterprise’s information system and adapt it to new challenges, including cyber threats and the need for technological updates. The main feature is the ability of the methodology to analyze the relationships between infrastructure components, taking into account digital coherence, which makes it possible to increase the accuracy of risk assessment and the efficiency of managing the information potential of the energy enterprise. Based on the data obtained, it is possible to assess the critical decrease in the level of information potential of the Zaporizhzhia Power Plant from 0.5790 to 0.3710 arbitrary units and its possible consequences for the efficiency of the enterprise